Human Costs of the Afghanistan War - Friesendorf, Cornelius; Müller, Thomas (Journal of Regional Security, 2018)
The war in Afghanistan has been the longest war in United States history. This article argues that from the beginning of the US-led invasion of Afghanistan in late 2001, the US conduct of the war posed great dangers for Afghan civilians. It distinguishes between three phases, each of which held distinct risks for civilians. The first phase, from late 2001 to 2009, was marked by the fight against al Qaeda and insurgent forces; the second phase, from 2009- 2010, by counterinsurgency; and the third phase by the transition of security responsibilities from NATO to Afghan security forces. While risk transfer clearly marked the first and third phases, civilians also suffered during the second phase, when the US put a primacy on civilian protection. We argue that neglecting civilian protection has not only been morally problematic but also risks undermining the Western goal of ensuring that Afghanistan will no longer pose a threat to international security.